Combining optical lithography with rapid microwave heating for the selective growth of Au/Ag bimetallic core/shell structures on patterned silicon wafers - Liu, Fu-Ken (Langmuir : the ACS journal of surfaces and colloids, 2005)
We demonstrate a novel approach for the production of patterned films of nanometer-sized Au/Ag bimetallic core/shell nanoparticles (NPs) on silicon wafers. In this approach, we first self-assembled monodisperse Au NPs, through specific Au...NH(2) interactions, onto a silicon substrate whose surface had been modified with a pattern of 3-aminopropyltrimethoxysilane (APTMS) groups to form a sandwich structure having the form Au NPs/APTMS/SiO(2). These Au NPs then served as seeds for growing the Au/Ag bimetallic core/shell NPs: we reduced silver ions to Ag metal on the surface of Au seeds under rapid microwave heating in the presence of sodium citrate. Energy-dispersive X-ray analysis confirmed that the Au/Ag bimetallic core/shell NPs grew selectively on the regions of the surface of the silicon wafer that had been patterned with the Au seeds. Scanning electron microscopy images revealed that we could synthesize well-scattered, high-density (>82%) thin films of Au/Ag bimetallic core/shell NPs through the use of this novel strategy. The patterned structures that can be formed are simple to produce, easily controllable, and highly reproducible; we believe that this approach will be useful for further studies of nanodevices and their properties